Perceived Effect of COVID-19 on the Health of Charcoal Producers in the Guinea Savannah Agro-Ecological Zone of Nigeria - P.O. Eniola (Archives of Current Research International, 2021)
Charcoal producers ignored the health implications of the activity especially during the COVID-19 pandemic resulting in several health disorders. Thus, the study examined perceived effect of COVID-19 on the health of charcoal producers in the derived savannah agro-ecological zone of Nigeria. Data were collected through the use of structured interview scheduled. A total of 178 respondents were selected using multistage sampling technique. Data were analysed through the use of frequency, mean, standard deviation and inferential statistics: chi-square and Analysis of Variance (ANOVA). The study reveals that most of the respondents strongly agreed that they usually use local herbs to treat all ailments during COVID-19. More than 50% of them always experienced difficult breathing during COVID-19, and that high death were recorded than before COVID-19 pandemic, while 88.2% of the respondents perceived low level of the effect of COVID-19 on their health. In addition, more than 50% of them strongly agreed that COVID-19 does not exist at all, that it is a taboo, while shaking hands with customers/friends is a symbol of love and that they cannot do without touching both face and nose during COVID-19 pandemic respectively. However, 93.3% of the respondents did not comply with the COVID-19 preventive measures. The study concludes that charcoal producers did not believe in the existence of COVID-19 and this may be dangerous to their health. Hence, education awareness on the hazard of COVID-19 to the health of charcoal producers should be encouraged.